Application Of Active Range Of Motion In Nursing Services And Care In Elderly With Stroke - Ayu Larasati; Ricky Riyanto Iksan; Buntar Handayani (Comprehensive Health Care, 2021)
Stroke is a big problem for the elderly in low-income countries (developing countries) than in high-income countries (developed countries). The Range of Motion Active stroke intervention is one of the non-pharmacological therapy efforts, exercises that are carried out to maintain or improve the level of perfection and the ability to move joints normally and completely to increase muscle mass and muscle tone. This study aims to identify the effect of providing Active Range of Motion exercise therapy in nursing services and care for the elderly with stroke problems. This type of research is a case study design research, which is a form of research (inquiry) or case studies and interventions about a problem that has a specificity (particularity). The results showed that the provision of Active Range of Motion was scored with the Pretest and Posttest scores. There is a change in the value of muscle strength in elderly stroke after being given Active Range of Motion exercise from the value of the muscle strength scale 2 to 3, 3 to 4, and 4 to 5. with data on the characteristics of stroke patients, namely age, gender and activities such as rarely exercising and not exercising repeatedly, this shows that the more frequent Active Range of Motion exercises can affect the assessment of muscle strength in stroke patients.